Posthumanist Feminism and Interspecies Affect in Nalo Hopkinson’s Midnight Robber - Martín-Lucas, Belén (Atlantis, 2017)
This paper examines the posthuman affective communities in Nalo Hopkinson’s dystopia Midnight Robber (2000), from an intersectional approach. It focuses on the interspecies affinity developed between a cyborg Black girl and other posthuman beings in outer space, where subaltern ‘artisans,’ machines, and indigenous communities provide nurturing affects of love and compassion that engender mutual respect and solidarity.